Bid Evaluation in the Construction Services Procurement Process - Tanubrata, Maksum (Jurnal Teknik Sipil, 2006)
In determining a contractor, project owners are usually interested in choosing the lowest bid, but that is not always true. For this reason, a bid evaluation is needed that can provide a fairly detailed description of the offers of each prospective contractor. Evaluation of bids from contractors is carried out by considering three aspects, namely: administrative aspects, technical aspects and price bidding aspects. These three aspects are evaluated one by one using a bid evaluation system by taking into account the requirements set by the consultant concerned. This case study contains data from the winning contractor, in this case PT Teguh Puncak Lestari and not the lowest bidder. This data includes administrative data, technical data and price bid data that will be used for bid evaluation. The system used in evaluating this bid is a value system, which is by assessing the administrative aspects, technical aspects and price bid aspects. In the value system, all requirements from the administrative aspect must be met first, then for the technical aspect and the price bid aspect are determined by a score. This score determines the winner of the tender. From the bid evaluation results, it turns out that PT Teguh Puncak Lestari has a complete administrative score, technical score = 60.50 and bid price value = 25.38. In evaluating bids, it is necessary to have staff who really master the technical aspects related to the project concerned.